The Urgency of External Supervision and the Ideal Model of Supervision of Constitutional Judges - Fuji SM Bako; Budiman Ginting; Faisal akbar Nasution; Afnila (Warmadewa Press, 2024)
External oversight of constitutional judges is a crucial element in maintaining the integrity and accountability of the constitutional judiciary system. The urgency of this oversight lies in its ability to prevent the abuse of power, enhance transparency, and strengthen public trust in the judiciary. In this context, external oversight functions as a control mechanism that helps ensure constitutional judges perform their duties in accordance with principles of justice and applicable law. However, effective external oversight requires an ideal and comprehensive model. The ideal oversight model should include key elements such as the independence of the oversight body, transparency of the oversight process, clear procedures for reporting and handling complaints, and accountability of the oversight body to the public. Additionally, public involvement in the oversight process is crucial to ensure that the oversight reflects the general interest. This study aims to evaluate the urgency of external oversight of constitutional judges and to develop an ideal oversight model that can enhance the effectiveness of external control. By implementing this model, it is hoped that the constitutional judiciary system can operate more fairly and accountably, and maintain public confidence in the constitutional judiciary.